Phonological syllabification in Danish once more: A propos Molbæk's paper - Basbøll, Hans (Annual Report of the Institute of Phonetics University of Copenhagen, 1980)
This paper contains an evaluation of Molbæk Hansen's critical discussion of my earlier syllabification principles of Danish phonology. A more recent version of the principles, which has been tested within the DANFON-project, is presented - although very sketchily - and Molbæk Hansen's counter-examples to the earlier principles are evaluated with respect to the DANFON-version. Particular attention is paid to the manifestation of short /a/, synchronically as well as diachronically.